2010
DOI: 10.1177/153303461000900408
|View full text |Cite
|
Sign up to set email alerts
|

Target Volume Delineation for Preoperative Radiotherapy of Rectal Cancer: Inter-Observer Variability and Potential Impact of FDG-PET/CT Imaging

Abstract: To analyze the inter-observer variability and the potential impact of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The magnitude of this uncertainty is determined by several factors such as images used for delineation (image modality, resolution, contrast, and windowing), human factors (experience of observers, their professional background), and the presence of the guidelines or atlases for contouring [3,4,11,32,35,43,50,52]. The introduction of multimodality imaging in planning and delivery process (CT, MR, PET-CT) gives further promise of better target definition [16,19,26,30,34,38,44,45,47].…”
Section: Critical Discussion Of Evaluation Parameters For Inter-obsermentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of this uncertainty is determined by several factors such as images used for delineation (image modality, resolution, contrast, and windowing), human factors (experience of observers, their professional background), and the presence of the guidelines or atlases for contouring [3,4,11,32,35,43,50,52]. The introduction of multimodality imaging in planning and delivery process (CT, MR, PET-CT) gives further promise of better target definition [16,19,26,30,34,38,44,45,47].…”
Section: Critical Discussion Of Evaluation Parameters For Inter-obsermentioning
confidence: 99%
“…The first group is based on descriptive statistics and contains parameters describing the distribution of volumes, such as mean, standard deviation, standard error, range, ratio of the largest drawn volume to the smallest one, and dispersion of the distribution, i.e., coefficient of variation (COV). COV is a popular parameter [2,13,19,25,26,43,51] as it provides the measure of dispersion of the distribution in a single number and can be easily correlated with other parameters of interest.…”
Section: Critical Discussion Of Evaluation Parameters For Inter-obsermentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies evaluated the variability in target volume delineation using descriptive statistics and parameters describing the distribution of volumes and diameters, such as mean, standard deviation, range, and dispersion of the distribution, such as COV [21][22][23][24][25][26][27][28]. The majority of studies deal with approaches that describe the overlapping area between contoured volumes, using metrics, such as CI and DC [22][23][24][26][27][28][29][30][31]. Moreover, when moving to 3D representation, metrics, such as variation of the COM, allow to evaluate the volume displacements in space [27,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This contouring process significantly reduces the interobserver variability in the interpretation of images, as it eliminates the human factor, increases consistency, and diminishes interobserver variability [ 42 , 43 ] . Krengli et al [ 44 ] analyzed the interobserver variation for target volume delineation in preoperative radiotherapy of rectal cancer, and concluded that PET/CT may allow a reduced interobserver variation in GTV delineation in comparison with CT. Buijsen et al [ 45 ] analyzed the effect of the use of PET/CT on the interobserver variation in GTV definition in rectal cancer. Forty-two patients diagnosed with rectal cancer underwent PET/CT for radiotherapy planning.…”
Section: Positron Emission Tomographymentioning
confidence: 99%